Attempted routes towards the synthesis of fluorinated analogues of ornithine as potential inhibitors of ornithine decarboxylase - De Villiers, Jandre (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2007.